An assumption of in situ resource utilization for “bio-bricks” in space exploration - Zuo, Hongyan; Ni, Shuisong; Xu, Meiying (Frontiers in Materials, 2023)
Microbially induced carbonate precipitation (MICP) mimics the natural cementation process that occurs in various geological settings by using the bicarbonate minerals resulting from various bacterial metabolic pathways as cementing agents. This bio-technique can be used to manufacture so-called “bio-bricks,” which rival regular bricks in strength and durability. In the last two decades, MICP has been increasingly utilized for the maintenance and repair of infrastructure. More recently, this process has also been shown to have great potential as an energy-saving and cost-effective means of in situ resource utilization (ISUR) to produce construction materials; these can be utilized for extraterrestrial human settlements for space programs such as lunar exploration. We thus review the description of natural cementation, the anaerobic and aerobic bacterial metabolic activities leading to calcium carbonate precipitation, the properties of the lunar regolith, the production of bio-bricks, and potential research needs.